2023
DOI: 10.1021/acs.est.3c02881
|View full text |Cite
|
Sign up to set email alerts
|

Desalination, Water Re-use, and Halophyte Cultivation in Salinized Regions: A Highly Productive Groundwater Treatment System

Abstract: Groundwater salinization is a problem affecting access to water in many world regions. Though desalination by conventional reverse osmosis (RO) can upgrade groundwater quality for drinking, its disadvantages include unmanaged brine discharge and accelerated groundwater depletion. Here, we propose a new approach combining RO, forward osmosis (FO), and halophyte cultivation, in which FO optimally adjusts the concentration of the RO reject brine for irrigation of Salicornia or Sarcocornia. The FO also reuses wast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Farzi et al [152] found that the halophytes Salicornia europaea, Salsola crassa, and Bienertia cycloptera had very good ability to reduce the water salinity of the con-structed wetlands. Halophytes can also be used to treat wastewater from industries such as oil and gas [153,154]. In addition, many halophytes are hyper-accumulators of heavy metals and therefore can be used for the phytoremediation of heavy-metalpolluted soils [155].…”
Section: Potential Uses and Importance Of Halophytes For Human Welfarementioning
confidence: 99%
“…Farzi et al [152] found that the halophytes Salicornia europaea, Salsola crassa, and Bienertia cycloptera had very good ability to reduce the water salinity of the con-structed wetlands. Halophytes can also be used to treat wastewater from industries such as oil and gas [153,154]. In addition, many halophytes are hyper-accumulators of heavy metals and therefore can be used for the phytoremediation of heavy-metalpolluted soils [155].…”
Section: Potential Uses and Importance Of Halophytes For Human Welfarementioning
confidence: 99%
“…Desalination of seawater and inland brackish water emerges as a promising solution to combat freshwater scarcity . However, limited by the low recovery ratio of the current desalination technologies, desalination plants produce substantial quantities of concentrated brine, the disposal of which poses significant environmental challenges, particularly concerning land vegetation and the aquatic ecosystem. , Thus, there has been a growing imperative toward maximizing reuse of liquid waste to achieve zero liquid discharge. , Zero liquid discharge necessitates the continuous concentration of water to a hypersaline state, which heightens demands on both materials and systems to effectively resist wetting and fouling issues …”
mentioning
confidence: 99%